Improving your Penetration Testing Skills : Strengthen your defense against web attacks with Kali Linux and Metasploit /: Strengthen your defense against web attacks with Kali Linux and Metasploit. (2019) - Najera-Gutierrez, Gilberto; Ansari, Juned Ahmed; Teixeira, Daniel; Singh, Abhinav
No abstract available